Kajian Potensi Refuse Derived Fuel (RDF) di Tempat Pembuangan Akhir (TPA) Cipayung untuk Memenuhi Baku Mutu Industri dan Ramah Lingkungan - Gathut Imam Gunadi; Taufik Nur Isman; Ridwan Alawi; Alvian Hadinata Tambunan; Prawoto; Eka Maulana (Jurnal Inotera, 2023)
The increased demand for energy is impacted by the growing population. As a result, new energy sources must be developed to replace the diminishing supplies. Waste to Energy (WTE) is a concept that can be used as an alternative to recycling waste into raw materials for Refuse Derived Fuel (RDF). Due to their combustibility, inorganic waste and plastic have the potential to be employed as source materials for RDF. In light of this discussion, RDF is required for both domestic and commercial purposes. chosen by classifying the garbage into different sizes and types. In order to demonstrate the huge potential for RDF treatment of active zone waste at the Cipayung Final Disposal Site (TPA), research has been conducted on the potential of RDF that meets industry standards and is environmentally friendly. From the analysis of available data, it is found that without using plastic and rubber waste, the calorific value of the RDF produced meets the required industry standards.